Phase I Study of Alternate‐Day Administration of S‐1, Oral Leucovorin, and Bevacizumab for Refractory Metastatic Colorectal Cancer. (17th June 2020) - Masuishi, Toshiki; Taniguchi, Hiroya; Komori, Azusa; Mitani, Seiichiro; Narita, Yukiya; Kadowaki, Shigenori; Ura, Takashi; Ando, Masashi; Muro, Kei
Abstract: Trial Information: Trial Identifier:  https://upload.umin.ac.jp/cgi-open-bin/ctr_e/ctr_his_list.cgi?recptno=R000018691UMIN000016094 Sponsor: Aichi Cancer Center Hospital Principal Investigator: Hiroya Taniguchi IRB Approved: Yes Click here to access other published clinical trials . Lessons Learned : The recommended S‐1 dose was 40 mg/m 2, twice daily on Monday, Wednesday, Friday, and Sunday, with oral leucovorin and bevacizumab. Compared with daily administration, the alternate‐day administration of S‐1 with oral leucovorin may reduce mucositis with promising antitumor activity in refractory metastatic colorectal cancer. Background: Daily S‐1 plus oral leucovorin administration in a 1‐week‐on/1‐week‐off schedule has promising efficacy in gastrointestinal cancer but is associated with high risk of mucositis and diarrhea. Methods: This phase Ib, 3+3 dose‐escalation trial included patients with chemorefractory metastatic colorectal cancer (mCRC) receiving S‐1 (40 mg/m 2 ) and leucovorin (25 mg) orally twice daily (level 1, even‐numbered days; level 2, Monday, Wednesday, Friday, and Sunday) and intravenous bevacizumab (5 mg/kg) every 2 weeks. Enrollment continued at the recommended dose level in the expansion cohort. Results: We enrolled 21 patients (3 and 18 patients in levels 1 and 2, respectively). Briefly, 12 and 9 patients had Eastern Cooperative Oncology Group (ECOG) performance status of 0 and 1, respectively, and 8 and 13 patients had 1–3 and ≥4 prior treatment lines, respectively. Dose‐limiting toxicity (DLT) was not observed, and level 2 was confirmed as the recommended dose. Common grade 3–4 adverse events at level 2 were anemia (22%), anorexia (6%), and diarrhea (6%). In the entire cohort, response rate, disease control rate, and median progression‐free survival were 10%, 71%, and 4.2 months, respectively. Conclusion: The recommended S‐1 dose was 40 mg/m 2, twice daily on Monday, Wednesday, Friday, and Sunday, with 25 mg oral leucovorin twice daily and 5 mg/kg bevacizumab every 2 weeks. Compared with the daily administration, alternate‐day administration of S‐1 plus leucovorin may reduce mucositis with promising antitumor activity in refractory mCRC.